2018
DOI: 10.1001/jamapsychiatry.2017.4741
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Associations Among Behavioral, Clinical, and Multimodal Imaging Phenotypes in Patients With Psychosis

Abstract: Multivariate analyses provide a more accurate characterization of the association between brain alterations and psychosis because they enable the modeling of other key factors that influence neuroimaging phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 99 publications
6
77
0
Order By: Relevance
“…Recent studies were consistent in recognizing P-BD as a subset with specific biological abnormalities in terms of genetic, immunological, endocrine, neurophysiological, brain imaging, and neuropsychological alterations, compared with both NP-BD and schizophrenia (Buoli et al, 2016;Moser et al, 2018;Palaniyappan et al, 2018). A growing body of literature has indicated that biological markers are most likely associated with the psychotic dimension in BD.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Recent studies were consistent in recognizing P-BD as a subset with specific biological abnormalities in terms of genetic, immunological, endocrine, neurophysiological, brain imaging, and neuropsychological alterations, compared with both NP-BD and schizophrenia (Buoli et al, 2016;Moser et al, 2018;Palaniyappan et al, 2018). A growing body of literature has indicated that biological markers are most likely associated with the psychotic dimension in BD.…”
mentioning
confidence: 83%
“…A growing body of literature has indicated that biological markers are most likely associated with the psychotic dimension in BD. Recent studies were consistent in recognizing P-BD as a subset with specific biological abnormalities in terms of genetic, immunological, endocrine, neurophysiological, brain imaging, and neuropsychological alterations, compared with both NP-BD and schizophrenia (Buoli et al, 2016;Moser et al, 2018;Palaniyappan et al, 2018). In regard to neuroimaging, the nonconsideration of this factor may contribute to the heterogeneous findings across studies of BD (Ellison-Wright & Bullmore, 2010).…”
mentioning
confidence: 87%
See 3 more Smart Citations